Therapeutic Targeting the Allosteric Cysteinome of RAS and Kinase Families - Li, Lianbo; Meyer, Cynthia; Zhou, Zhi-Wei; Elmezayen, Ammar; Westover, Kenneth (Journal of molecular biology, 2022)
[Display omitted] •Allosteric inhibitors have many theoretical advantages including superior selectivity, the ability to modulate allosteric biological processes, and the ability to fine-tune biological responses.•Allosteric KRAS G12C inhibitor development showed that covalent chemistry can convert a suboptimal binding pocket into a druggable pocket.•In this review, we review the broader history of allosteric inhibitor development in the RAS and kinase fields and identify opportunities to accelerate allosteric drug development by leveraging covalent chemistry targeting cysteines. Allosteric mechanisms are pervasive in nature, but human-designed allosteric perturbagens are rare. The history of KRASG12C inhibitor development suggests that covalent chemistry may be a key to expanding the armamentarium of allosteric inhibitors. In that effort, irreversible targeting of a cysteine converted a non-deal allosteric binding pocket and low affinity ligands into a tractable drugging strategy. Here we examine the feasibility of expanding this approach to other allosteric pockets of RAS and kinase family members, given that both protein families are regulators of vital cellular processes that are often dysregulated in cancer and other human diseases. Moreover, these heavily studied families are the subject of numerous drug development campaigns that have resulted, sometimes serendipitously, in the discovery of allosteric inhibitors. We consequently conducted a comprehensive search for cysteines, a commonly targeted amino acid for covalent drugs, using AlphaFold-generated structures of those families. This new analysis presents potential opportunities for allosteric targeting of validated and understudied drug targets, with an emphasis on cancer therapy.